The secret world of haute couture - Kinmonth, Margy (Australia : BBC Active, 2006)
In a journey which takes her from PAris to New York and Los Angeles, filmmaker Margy Kinmonth meets millionaire customers and world famous designers as she explores the Haute Couture fashion industry
Title from title screen
Executive producer, Tracy Jeune ; camera, Patrick Duval, Mark Molesworth ; sound, Daniel Brooks ; editor, Guy Crossman, Jeff Shaw
DVD Format
Keywords: Fashion; Costume design; Fashion designers